Sustainable planning and management of water users associations for enhanced agriculture / B. Anuradha and V. Mohan - Anuradha, B.; Mohan, V. (2012)
Irrigation tanks in India are common property resources. Conservation of water in the agricultural sector is essential since water is necessary for the growth of plants and crops. Farmer’s Organizations need to be empowered to assess the irrigation coverage. WUA is a group of water users, such as irrigation; who pool their financial, technical, material and human resources for the operation and maintenance of a water system. Proper usage of available sources of water by dynamic WUA gives best result in terms of increased cultivated areas in tank command. Hence two tanks namely, Pillapakkam and Irumbedu (villages with active WUA) of Kancheepuram district, Sriperambathur taluk in Tamilnadu were selected for this study to probe the impact made by active WUAs on agricultural productivity. Primary data was collected through interview schedules and analysed using Statistical Package for Social Science (SPSS). Expected result gives the regression equation for farm size, income and expenditure. Hence it is necessary to form a new WUA in the villages where it has not yet been established. Also WUA should be revived in places where it is not functioning well for improved livelihood of village people.